Pengaruh Efektivitas Organisasi terhadap Kinerja Pegawai (Studi Kasus dalam Penerapan E-Lppd Di Sekda Kota Binjai) - Harahap, Ayani Putri Asa Walidaini; Irmayani, Tengku; Ridho, Hatta (PERSPEKTIF, 2024)
The Government of Indonesia strives to improve effectiveness and efficiency in governance by implementing the Electronic-Based Government System (SPBE) as stipulated in Presidential Regulation Number 95 of 2018. One of its implementations is the Electronic-Report on Local Government Administration (E-LPPD), which replaces manual reports. This study aims to examine the effect of the implementation of E-LPPD on employee performance at the Binjai City Regional Secretariat. The research method used is quantitative with the population of all authorized apparatuses and has implemented E-LPPD in Binjai City, totaling 87 people. The sampling technique uses saturated samples. The results showed that environmental characteristics in the implementation of E-LPPD had a significant effect on employee performance, while organizational characteristics, employees, and management policies and practices did not show a significant influence. Overall, implementing E-LPPD positively affects employees' performance at the Binjai City Regional Secretariat. These findings emphasize the importance of adequate environmental adjustments and support to optimize performance through electronic systems in local government.